Safety and effectiveness of vortioxetine for major depressive disorder: Real-world evidence from a population-based study in South Korea - Moon, Seok Woo; Kim, Jee Wook; Kim, Do Hoon; Lee, Kyu Young; Reines, Elin Heldbo; Lee, Minah; Park, Yoo Jin (Frontiers in Psychiatry, 2023)
Background: A post-marketing surveillance study was conducted to assess the real-world safety and effectiveness of vortioxetine for the treatment of major depressive disorder (MDD) in South Korea. Methods: Adult patients aged 19–94 years receiving vortioxetine for MDD at 72 hospitals and clinics in South Korea between 19th August 2014 and 18th August 2020 were included. Patients were followed for up to 24±2 weeks, at up to three visits. Adverse events (AEs) and effectiveness, assessed by both clinician and patient-reported measures, were analyzed. Results: A total of 3,263 patients (mean age: 51.28 years) were included in the safety set; 1,095 were aged ≥65 years. The majority of the safety set (61.97%) were female. The overall rate of any AEs and serious AEs were 17.13% and 1.56%, respectively. The majority of AEs were mild (88.32%). The rates of AEs did not differ statistically by age (≥65 years: 16.89% [185/1,095] versus <65 years: 17.25% [374/2,168)], p=0.7989), sex (male: 15.95% [198/1,241] versus female: 17.85% [361/2,022], p=0.1623) or liver impairment (with liver impairment: 20.90% [14/67] versus without liver impairment: 17.05% [545/3,196], p=0.4087). Effectiveness was assessed in 1,918 patients. By 24±2 weeks, there were significant clinical improvements from baseline, assessed by change in Montgomery-Asberg Depression Rating Scale total score (mean±standard deviation [SD]: -10.49±9.42 points, p<0.0001), the proportion of patients with improved symptoms using the Clinical Global Impression - Improvement scores (79.29%), and in both patient-reported measures, with a significant improvement in the Korean Version of the Perceived Deficits Questionnaire-Depression (mean±SD: -6.06±13.23, p<0.0001) and Digit Symbol Substitution Test (mean±SD: 4.83±9.81, p<0.0001) total scores from baseline. Similar to the safety profiles, the proportions of patients with improved symptoms compared with baseline using the Clinical Global Impression - Improvement scores did not differ by age (≥65 years: 82.09% versus <65 years: 78.32%, p=0.0511), sex (male: 77.45% versus female: 81.01%, p=0.0587), or liver impairment (with liver impairment: 67.57% versus without liver impairment: 79.85%, p=0.0663). Conclusions: Vortioxetine appears to be well-tolerated and effective for treating MDD patients in the real-world setting in South Korea, irrespective of age, sex, and liver impairment, reflecting the known profile of vortioxetine based on studies worldwide.